High Tibial Osteotomy for knee joint preservation: “Old but Gold”! - Santoso, Asep; Phatama, Krisna Yuarno; Rhatomy, Sholahuddin; Budhiparama, Nicolaas Cyrillus (The Hip and Knee Journal, 2023)
One of the most common chronic diseases affecting the elderly is knee osteoarthritis (OA) that significantly impairs the activity of the daily living. Change of mechanical axis of the knee causes impairment on the three compartments of knee. If the medial compartment is affected, it will cause varus knee deformity, whereas, involvement of lateral compartment will result in valgus knee deformity. Deformities of angular and/or rotational nature can be corrected using the knee osteotomy technique, consequently realigning the bone axis.The osteotomy technique has been developed for centuries. Current growing interest in developing minimally invasive techniques for high tibial osteotomy (HTO) using smaller incisions, arthroscopy-assisted osteotomy, patients specific instrumentation (PSI) and computer-guided navigations systems. These techniques aim to reduce surgical trauma, minimize scarring, and facilitate faster recovery.